Entreprenurial Engagements In Youth Samples: Examining The Predictive Role Of Risk Tolerance - Sunday A. Atunwa; Chidinma P. Nebo; Emmauel E. Uye (International Journal of Technology and Education Research, 2026)
Youth entrepreneurial engagements have become increasingly vital in addressing economic challenges and unemployment issues in many parts of Nigeria. While studies have examined different predictors of entrepreneurial engagements with varied results, studies linking risk tolerance directly to entrepreneurial engagements among youth samples are lacking. Therefore, this study examines the predictive role of risk tolerance on entrepreneurial engagement among youth samples in Rivers State, Nigeria. Cross-sectional survey design was adopted while purposive sampling technique was used to select the study population. Data were collected from 219 youths using validated questionnaires and analyzed using simple linear regression to test one hypothesis that was accepted at p < .001 level of significance level. The result demonstrates significant influence of risk tolerance on entrepreneurial engagement among study participants, R2 =.411, F (1,218) = 42.96, p <.001. In addition, the result reveals that risk tolerance independently predicts entrepreneurial engagement among study participants (β = .622, p <.001). The study concludes that risk tolerance is an important predictor of entrepreneurial engagement among youth samples. The study recommends that government agencies, non-governmental organizations, and higher institutions should design and implement entrepreneurship development programs that would explicitly enhance risk tolerance among the youth population.